Astragaloside IV and Saponins of Rhizoma Polygonati Cure Cyclophosphamide-Induced Myelosuppression in Lung Adenocarcinoma via Down-Regulating miR-142-3p - Gu, Xian; Zhu, Ling-yu; Xu, Zhen-ye; Shen, Ke-ping (Frontiers in Oncology, 2021)
Our previous study revealed that Shuanghuang Shengbai granule could cure the myelosuppression induced by cyclophosphamide (CTX) in lung cancer. However, its hematopoietic effects and molecular mechanisms remain not fully understood. Therefore, the study was intended to investigate the effects and the underlying mechanisms of Astragaloside Ⅳ(AS) and saponins of Rhizoma Polygonati (SRP), the two main bioactive ingredients of Shuanghuang Shengbai granule, on CTX-induced myelosuppression. CTX inhibited the proliferation and promoted apoptosis in bone marrow hematopoietic stem cells (BMHSCs), and accompanied by increased the expression of miR-142-3p; AS and/or SRP treatment could alleviate CTX-induced cell injury, and suppressed the expression of miR-142-3p. Over-expression of miR-142-3p partially reversed the therapeutic effect of AS and/or SRP on CTX-induced cell injury in BMHSCs. Further mechanism exploration discovered that HMGB1 was the target gene of miR-142-3p, and miR-142-3p negatively regulated the expression of HMGB1. To further explore the function of AS and/or SRP in vivo, we constructed a lung cancer xenograft combined with CTX-induced myelosuppression mouse model. And we found that AS and SRP remarkably reversed CTX-induced the reduction of white blood cells (WBCs), bone marrow nucleated cells (BMNCs), and thymus index in vivo, and did not affect the chemotherapy effect of lung cancer. Collectively, our results strongly suggested that AS and SRP could improve the hematopoietic function of myelosuppressed lung cancer mice, and their effects may be related to the inhibition of miR-142-3p expression in BMHSCs.